Patriotic Thought of Ngo Thi Nham – An Approach from the Perspective of Vietnamese Patriotic Culture in the 18th Century - Hang, Le Thuy; Phuong , Nguyen Van (Journal of Cultural Analysis and Social Change, 2025)
Ngo Thi Nham (1746 - 1803) was a prominent Vietnamese scholar official whose life and thought embodied the transformation of patriotic culture in 18th-century Vietnam. Living through the decline of the Le–Trinh regime and the disintegration of Confucian orthodoxy, he confronted a period marked by social unrest, foreign aggression, and moral crisis. This study examines Ngo Thi Nham’s patriotic thought through the lens of Vietnamese cultural traditions of patriotism, emphasizing how he redefined the moral foundations of loyalty and national identity. Employing historical–philosophical and cultural analysis, the article identifies three key dimensions of his patriotic philosophy: the principle of relieving the people’s burdens as a form of serving the nation; the reinterpretation of loyalty, shifting from fidelity to a dynasty toward devotion to the people and the survival of the country; and the affirmation of national pride through the preservation of Vietnam’s cultural autonomy and moral integrity. By situating Ngo Thi Nham within the broader evolution of Vietnamese patriotic culture, this study elucidates how his ideas reflected a transition from feudal loyalty to cultural nationalism, thereby enriching the intellectual heritage of Vietnamese patriotism and contributing enduring values to the nation’s philosophical tradition.